Faktor Internal, Makroekonomi dan Pembiayaan Bermasalah Bank Syariah di Indonesia - Ardana, Yudhistira (Esensi: Jurnal Bisnis dan Manajemen, 2019)
Non Performing Financing is the most important issue for banks to survive. This study aims to analyze the determination of internal and external factors on Non Performing FInancing on Sharia Banking in Indonesia. This study uses Error Correction Model analysis techniques. The results show that in the short term the variables that have a significant effect on Non Performing Financing on Sharia Banking in Indonesia are inflation variables, while the Exchange Rate, Bank Indonesia Certificate of Wadi’ah, Industrial Production Index, Financing Deposite Ratio, and Capital Adequacy Ratio variables have no significant effect. In the long run the variables that are influential are Exchange Rate, Bank Indonesia Certificate of Wadi’ah, Financing Deposite Ratio, and Capital Adequacy Ratio, while Inflation and Industrial Production Index have no significant effect.